THE POLITICS OF CRIMINAL LAW IN CYBERCRIME: AN EFFORTS TO COMBAT INFORMATION TECHNOLOGY CRIMES IN INDONESIA - Milla Mudzalifah; Pujiyono Pujiyono (UNISSULA, 2023)
This article aims to analyze the politics of criminal law in cybercrime and its efforts to overcome information technology crimes from cybercrime. This article used a normative juridical approach. This study concludes that legal politics has a significant role in enforcing the Information and Electronic Transaction Law because it is related to the existence of political will in enforcing the Aquo Law, where there is a structure that is very closely related to legal politics. Efforts to deal with information technology crime, as stated in the Preamble to the 1945 Constitution paragraph 4, to date, two cyber laws of the Electronic Information and Transaction Law have been and are or are still in force in Indonesia. Changes to the cyber law of the Information and Electronic Transaction Law occur because of the influence of legal politics, which is the primary policy in determining the direction, form, and content of the law to be formed following the needs of the state at the time the law is enacted and the politics of the government's interests at the time an Act applies.